Pulse plasma nitrocarburising of gas shock absorber tubes from steel W.No. 1.0116 - Leskovšek, Vojteh (Kovine zlitine tehnologije, 1997)
Gas shock absorber tubes from steel W.No. 1.0116 were pulse plasma nitrocarburised at 560 and 580°C in atmosphere containing carbon dioxide additions. Variations in compound layer structure, thickness, porosity, hardness-depth profiles and stability of the process were investigated. It was found that the formation of preadominantly ?$ε$?phase compound layer structure is promoted by high nitrogene atmosphere. The compound layer thickness was found to increase nitrogen content, temperature, and pulse as well as decreasing carbon dioxide content. The experiments showed that by use of high nitrogene atmosphere no pores appear in compound layers on steel W.No. 1.0116. Proper process control and the addition of carbon dioxide to the atmosphere with high content of nitrogene result in a reasonably thick compound layer from predominantly ?$ε$?phase.
Keywords: jekla; nitriranje v plazmi; technology; tehnologija; fazni diagrami; struktura; debelina; poroznost; trdota